Systematic review with meta-analysis: conditioned pain modulation in patients with the irritable bowel syndrome - Albusoda, Ahmed; Ruffle, James K.; Friis, Kathrine A.; Gysan, Maximilian R.; Drewes, Asbjørn M.; Aziz, Qasim; Farmer, Adam D. (Alimentary pharmacology & therapeutics, 2018)
Background Irritable bowel syndrome (IBS) is common and is characterised by recurrent abdominal pain, which is a major contributor to healthcare seeking. The neurobiological basis of this pain is incompletely understood. Conditioned pain modulation is a neuromodulatory mechanism through which the brain inhibits the nociceptive afferent barrage through the descending pathways. Reduced conditioned pain modulation has been implicated in the pathophysiology of IBS, although to date only in studies with relatively small sample sizes. Aim To clarify the relationship between conditioned pain modulation and IBS by undertaking a systemic review and meta-analysis Methods A systematic review of MEDLINE and Web of Science databases was searched (up to 10 May 2018). We included studies examining conditioned pain modulation in adults with IBS and healthy subjects. Data were pooled for meta-analysis to calculate the odds ratio and effect size of abnormal conditioned pain modulation in IBS, with 95% confidence intervals (CI). Results The search strategy identified 645 studies, of which 13 were relevant and 12 met the inclusion criteria. Conditioned pain modulation in IBS patients vs healthy subjects was significantly reduced, odds ratio 4.84 (95% CI: 2.19-10.71, P < 0.0001), Hedges’ g effect size of 0.85 (95% CI: 0.42-1.28, P < 0.001). There was significant heterogeneity in effect sizes (Q-test χ2 = 52, P < 0.001, I2 = 78.8%) in the absence of publication bias. Conclusion Conditioned pain modulation is significantly diminished in patients with IBS vs healthy controls. These data suggest that abnormal descending pathways may play an important pathophysiological role in IBS, which could represent an investigation and a therapeutic target in IBS.